Mennonites and deforestation in South America - Dourojeanni, Marc (2022)
Mennonites migrated to South America in considerable numbers after World War II and have settled in several countries, but mainly in Paraguay and Bolivia where they developed large agricultural enterprises, occupying forests and other natural ecosystems. It is estimated that they deforested over four million hectares of the Chaco and Chiquitania biomes, mainly for livestockand soybean. Since the current century they began to invade the Amazon of Bolivia and more recently those of Peru and Colombia, having already deforested probably around twenty thousand hectares. Given its antecedents in Mexico and Central America, as well as in Paraguay and Bolivia, there is also concern that its tactics to occupy the land, as well as many of its practices, may be largely illegal and harmful to both the environment and local population, especially indigenous people. Recent evidence from Peru and Colombia confirms these suspicions.